The impact of diabetes mellitus on coronary artery disease: new therapeutic approaches. - Tousoulis, D; Kampoli, A; Papageorgiou, N; Papaoikonomou, S; Antoniades, C; Stefanadis, C (2009)
Patients with diabetes mellitus (DM) type 2 have a high prevalence of coronary artery disease (CAD), as diabetes is implicated in the formation of atherosclerotic plaque. Hyperglycemia, elevated free fatty acid, increased amount of circulating end-glucosylated serum products and insulin resistance are the main mechanisms involved in the accelerated atherosclerotic process observed in type 2 DM patients. Novel treatments have been proposed to prevent and treat CAD in patients with diabetes, mainly in those with diabetes type 2. Several clinical trials have been designed in order to examine the effectiveness of these agents, such as angiotensin-converting enzyme inhibitors and angiotensin II receptor blockers, glitazones, statins and antioxidants, but the results are still controversial.